2012
DOI: 10.1177/0891988712436688
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Effects on Creatine Kinase Activity and Mood in Geriatric Bipolar Depression

Abstract: Introduction Despite the prevalence, associated comorbidities, and functional consequences of bipolar depression (BPD), underlying disease mechanisms remain unclear. Published studies of individuals with bipolar disorder implicate abnormalities in cellular energy metabolism. This study tests the hypotheses that the forward rate constant (kfor) of creatine kinase (CK) is altered in older adults with BPD and that CoEnzyme Q10 (CoQ10), known to have properties that enhance mitochondrial function, increases kfor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…Reduction in CK activity may potentially impair energy homeostasis, leading to cell death (Aksenov et al, 2000). However, despite the fact that depression in humans and in animal models did not alter brain CK activity Forester et al, 2012), similar to the present results, chronic administration of some antidepressants, such as imipramine and paroxetine, increased CK activity in the rat brain (Santos et al, 2009;Réus et al, 2012). From these results, it can be hypothesized that enhancing mitochondrial function and CK activity may present an opportunity for the development of a potentially more efficient pharmacotherapy against depressive disorders.…”
Section: Adrenal Gland Wet Weight (Mg)supporting
confidence: 79%
See 1 more Smart Citation
“…Reduction in CK activity may potentially impair energy homeostasis, leading to cell death (Aksenov et al, 2000). However, despite the fact that depression in humans and in animal models did not alter brain CK activity Forester et al, 2012), similar to the present results, chronic administration of some antidepressants, such as imipramine and paroxetine, increased CK activity in the rat brain (Santos et al, 2009;Réus et al, 2012). From these results, it can be hypothesized that enhancing mitochondrial function and CK activity may present an opportunity for the development of a potentially more efficient pharmacotherapy against depressive disorders.…”
Section: Adrenal Gland Wet Weight (Mg)supporting
confidence: 79%
“…Coenzyme Q10 (CoQ10), a lipid-soluble benzoquinone present in the phospholipid bilayers of mitochondria, is known to boost mitochondrial function. Accumulating evidence suggests a protective therapeutic role of CoQ10 in some neurodegenerative disorders, for example, Alzheimer's disease (Littarru and Tiano, 2007), Parkinson's disease (Hargreaves et al, 2008), epilepsy (Tawfik, 2011), and major depression (Forester et al, 2012). CoQ10 is a ubiquitous compound, found in the highest concentrations in tissues with high energy turnover such as the brain and heart (Beal, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…34 Therefore, further investigation into the exact mechanism(s) of action of NAC is warranted. Recently, an open-label study of CoQ10 in geriatric patients with bipolar depression demonstrated antidepressant effects early in treatment, which dissipated by the end of the 8-week study, 45 supporting further investigation in larger controlled trials.…”
Section: Discussionmentioning
confidence: 87%
“…Following IRB approval, subjects were recruited to participate in two studies investigating the bioenergetic effects of CoQ10 utilizing a 31 P-MRS protocol at 4 Tesla (T) 16 (Forester, unpublished). Subjects met DSM-IV TR criteria for Bipolar Disorder, Type I or II, current episode depressed, and were excluded with any previous or current co-morbid Axis I disorder, unstable medical illness, untreated thyroid dysfunction, a history of substance abuse within the past year, Young Mania Rating Scale (YMRS) score of > 6, or Montgomery Asberg Depression Rating Scale (MADRS) < 18.…”
Section: Methodsmentioning
confidence: 99%